A dual treatment blocks alcohol binge-drinking relapse: Microbiota as a new player. (1st July 2022) - Ezquer, Fernando; Quintanilla, María Elena; Morales, Paola; Santapau, Daniela; Munita, José Manuel; Moya-Flores, Francisco; Ezquer, Marcelo; Herrera-Marschitz, Mario; Israel, Yedy
Abstract: Rationale: Gut microbiota communicates information to the brain. Some animals are born with a gut microbiota that predisposes to high alcohol consumption, and transplantation of fecal material from alcoholics to mice increases animal preference for ethanol. Alcohol-use-disorders are chronic conditions where relapse is the hallmark. A predictive animal model of relapse is the "alcohol deprivation effect" where ethanol re-access is allowed following chronic alcohol intake and a long alcohol deprivation. The present study evaluates the effect of gut microbiota modification on relapse, as an adjunct to N-acetylcysteine + Acetylsalicylic acid administration, which inhibits the alcohol-induced hyper-glutamatergic condition. Methods: Rats bred as heavy alcohol consumers (UChB) were allowed ethanol intake for one month, were deprived of alcohol for two-weeks and subsequently offered re-access to ethanol. Prior to ethanol re-access animals received orally either (i) vehicle-control, (ii) L actobacillus-rhamnosus -GG after antibiotic treatment (LGG); (iii) N-acetylcysteine+Acetylsalicylic acid (NAC/ASA) or (iv) both treatments: LGG+ (NAC/ASA). Results: Marked binge drinking (1.75 g ethanol/kg in 60 min) and blood alcohol levels exceeding 80 mg/dl were observed in the control group upon ethanol-re-access . Lactobacillus -GG or (NAC+ASA) treatments inhibited alcohol intake by 66–80%. The combination of both treatments virtually suppressed (inhibition of 90%) the re-access binge-like drinking, showing additive effects. Treatment with NAC+ASA increased the levels of glutamate transporters xCT and GLT-1 in nucleus accumbens, while Lactobacillus-GG administration increased those of the dopamine transporter (DAT). Conclusions: The administration of a well-accepted probiotic may be of value as an adjunct in the treatment of alcohol-use-disorders. Graphical Abstract: Gut microbiota strongly influences ethanol relapse. Ethanol relapse intake following ethanol deprivation and re-access was significantly inhibited by the oral administration of Antibiotic/Lactobacillus. When combined with N- acetylcysteine + Acetylsalicylic acid ethanol relapse was 90% inhibited. ga1